Counter-Guerrilla Operations : The Philippine Experience - Valeriano, Napoleon D. and Bohannan, Charles T. R. (London Pall Mall Press, 1962)
This volume in the Praeger Security International (PSI) series Classics of the Counterinsurgency Era by two officers-one from the Philippines and the other from America-who fought as guerrillas against the Japanese occupation and went on to defeat the Huk rebellion after World War II. Unlike many other accounts of counterinsurgency operations that focus on theoretical principles and their tactical applications, the authors examine the means to assess the strengths and weaknesses of insurgencies. An enduring contribution of this book is its emphasis on the importance of intelligence in combatin.
Include Appendix
Keywords: Guerrilla warfare -- Hukbong Mapagpalaya ng Bayan (Philippines) -- HISTORY -- Military -- Strategy